Assessing the EffectivenessRole of ZakatManagement on Income Inequality in Selangor - Mohd Rahim Khamis; Maryam jameelah Hashim; AzmanAb Rahman (Universiti Sains Islam Malaysia, 2024)
Ulum Islamiyyah, Volume 36 Issue 03 Page (26–37)